DEVELOPMENT OF A PELTIER TYPE CLOUD CHAMBER WITH WIDE VIEW FIELD. Issue 3 (26th April 2019) - Toda, Takehiro; Hasan, Md Mahamudul; Igarashi, Yu; Katengeza, Estiner W; Iimoto, Takeshi
Abstract: Cloud chamber contributes to radiation education by facilitating observation of particle tracks formed by radiation. Peltier-based chamber achieves cooling without the need for dry ice, . we developed a cloud chamber based on peltier thermoelectric modules and has a multilayered heat insulation system to maintain a stable cool environment. It produces sharp particle tracks without requiring a dark room for observing the tracks. Its large top window (diameter of 12.5 cm) provides a relatively wider observation field capable of accommodating five to six students at a time.